KARAKTERISTIK NUHAT KUFAH DAN BASHRAH - Ridwan, Ridwan (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2008)
Nahwu have an important position for study literatures which written by Arabic. That is why it set in context. Arranged for the first time by Abu al-Aswad al-Duâ€™ali with the instruction and agreement of Ali R.A. In first, nahwu was born inÂ Bashrah, the great city and the complete metropolis, made illustrious by Sibawaih and al-Khalil b. Ahmad in Particular, occurred still in this city. Than, nahwu became depeloved and expanded to various city like Kufah, Baghdad, Mesir, and Andalusia.